Elemental mapping and quantitative characterization of dendrite structure in IN718 supperalloy based on micro beam X-ray fluorescence and EPMA. (April 2022) - Li, Dongling; Cai, Wenyi; Liu, Zongxin; Shen, Xuejing; Wang, Haizhou; Zhu, Guoliang; Shu, Da
Abstract: Micro beam X-ray fluorescence (μ-XRF) has been applied to characterize the quantitative distribution of elements in the dendrite structure of IN718 superalloy for the first time with the advantage of simple sample preparation, no requirement for conductivity, high spatial resolution and non-destructive surface. Dendrite structure is an important microstructure in cast polycrystalline superalloys such as IN718 superalloy. In this paper, the distribution characterization of Ni, Cr, Fe, Nb, Mo and Ti in the dendrite structure of superalloy was performed by μ-XRF with the improvement of the quantitative method. The elemental mapping with higher spatial resolution in the dendrite structure was obtained by electron probe micro-analysis (EPMA). The elemental content distribution on primary dendrite arm, secondary dendrite arm and inter-dendritic zone of superalloy was investigated and the segregation ratios of different elements have been obtained. It was found that the elemental distribution in dendrite structure of IN718 alloy was inhomogeneous and the content of Nb, Mo and Ti was much higher than that on dendrite arm and the elements of Fe, Cr and Ni have the opposite distribution tendency. Severe micro segregation of Nb has been revealed on the dendrite structure. The minimum Nb value of 2.90 wt%, the mean Nb value of 4.90 wt% and the maximum value of 8.84 wt% in the tested IN718 superalloy sample determined by μ-XRF have good agreement with the composition data of key nonequilibrium point in the Pseudo-binary solidification constitution diagram of Inconel 718. The content distribution of alloy elements (Mo, Nb and Ti) presents a sine distribution between the secondary dendrite arm and inter-dendritic region and the average SDAS value obtained from the line content distribution figure is about 70–80 μm. The segregation ratio of different elements has obtained and the SR values of Nb and Ti are much greater than 1. There were some large precipitates particles containing Nb and Ti elements distributed on the inter-dendritic zone, which led to the fluctuation of Nb and Ti contents. Highlights: Elemental quantitative distribution characterization method of dendrite structure in superalloy is studied by μ-XRF. Elemental mapping and line distribution analysis are performed. Nb, Mo, Ti elements are enriched on the inter-dendritic zones. Microsegregation variation for Fe, Ni, Cr, Nb, Mo, Ti in dendrite structure is investigated.